Blood parameter and histopathological changes in osteoporotic rat model treated with cockle shell - derived calcium carbonate nanocrystals - Jaji, Alhaji Zubair (2016)
Osteoporosis is a chronic systemic metabolic condition characterized by decreased density of normally mineralized bone due to faulty remodeling process. The success of age long studies on the prevention and treatment of osteoporosis have always been hindered by the ineffectiveness and hazards of the therapeutics and routes of administration used. Nanotechnology is poised to address these issues. This study was aimed at investigating the effectiveness of cockle shell-derived CaCO3 nanocrystals aragonite polymorph as a therapeutic and a hormonal-carrier in the management of primary osteoporosis. Standard techniques were used in the synthesis and evaluations of physicochemical and in vitro/in vivo potentials and safety of ANC and the human recombinant parathyroid hormone (PTH 1-34) - loaded ANC (PTH-ANC) for the management of primary osteoporosis.Transmission Electron Microscopy (TEM) and Field Emission Scanning Electron Microscopy (FESEM) results demonstrated highly homogenized spherical-shaped aragonite nanocrystals of 30±5 nm in diameter. PTH-ANC had a Zeta potential of -27.6 ± 8.9 mV. The encapsulation efficiency of the formulation were found to be directly proportional to the concentrations of the drug fed. The X-ray diffraction (XRD) patterns revealed strong crystallizations with no positional change of peaks before and after PTH-ANC synthesis. Fourier Transform Infrared (FT-IR) spectroscopy demonstrated no detectable interactions between micron aragonite and surfactant at molecular level. PTH-ANC formulation was stabilized at pH 7.5, enabling sustained slow release of PTH 1-34 for 168 hours (one week). A 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) cytocompatibility assay in Human Foetal Osteoblast Cell Line hFOB 1.19 showed that ANC can safely support osteoblast proliferation up to 48 hours while PTH-ANC can safely support the proliferation at 72 hours and beyond due to the sustained slow release of PTH 1-34. A14 day acute toxicity and repeat dose 28 day trial studies of ANC in Sprague Dawley rats recorded no mortality. However, significant haematological anomalies, clinical signs and gross and histopathological lesions were recorded in the acute toxicity groups and the high dose (1g/kg body weight) and medium (0.1 g/kg/kg body weigh) toxicity groups of the repeat dose 28 day trial study. The low dose groups (0.01 g/kg body weight) recorded mild. In vivo efficacy evaluation of antiosteoporotic and drug delivery efficacy of ANC and PTH-ANC demonstrated significant interactions between treatments and regimens. Daily administration of ANC or PTH 1-34, and weekly and fortnightly administrations of PTH-ANC, enabled best gains in bone mass density and strength in ovariectomized and orchidectomized rats. These were consistently demonstrated by results from proliferation and resorption proteomic analyses, bone morphometry and densitometry, flexural 3 point biomechanical bending test, serum calcium and phosphorus analyses, bone ash, calcium and phosphorus analyses and immuhistochemistry. It was concluded that due to its biogenic nature, ANC is a biocompatible antiosteoporotic agent with a cheap method of synthesis. It doubles as a nanocarrier for the enhancement of efficacy and safety of the bone anabolic PTH 1-34. ANC will reduce the cost, dosage and dose frequency associated with the use of PTH 1-34 management of primary form of osteoporosis and enable better compliance to its prescriptions.